Peran kelompok sadar wisata Tuk Kumala dalam pengembangan desa wisata Kalilunjar di Kabupaten Banjarnegara - Saputri, Meylanda; Wijaya, Atika (Ecotourism and Environment Conservation, 2024)
Introduction: Pokdarwis is a community-based organization that aims to assist the government in efforts to develop village tourism. This article discusses the role played by Pokdarwis Tuk Kumala in efforts to develop the Kalilunjar Tourism Village. Method: This study uses qualitative methods with data collection techniques through observation, interviews, and documentation. This article is presented in a descriptive form using the role concept. Result: The results showed that the role of Pokdarwis Tuk Kumala in tourism development in Kalilunjar Village was developing tourism potential and managing tourism businesses, increasing the Human Resources of Pokdarwis Tuk Kumala members and the people of Kalilunjar Village, collaborating with the private sector, and preserving the traditions of Kalilunjar Tourism Village. In carrying out its role, Pokdarwis Tuk Kumala does not walk alone, but has received support and assistance from the Kalilunjar Village Government, the Culture and Tourism Office of Banjarnegara Regency, and the people of Kalilunjar Village and private sector. Conclusion: Based on the results of this study, it can be concluded that the Pokdarwis Tuk Kumala in carrying out its role is assisted by the local community, the Kalilunjar Village Government, and the Culture and Tourism Office of Banjarnegara Regency, and private sector.